Alkaline‐Earth‐Metal‐Catalyzed Thin‐Film Pyrolysis of Cellulose. Issue 4 (14th January 2016) - Zhu, Cheng; Maduskar, Saurabh; Paulsen, Alex D.; Dauenhauer, Paul J.
Abstract: The conversion of lignocellulosic biomass to "bio‐oils" by thermochemical pyrolysis is a promising reactor technology for renewable chemicals and biofuels. Although the fundamental understanding of relevant catalysts within reacting biomass particles is only in its infancy, it is known that inorganic materials naturally present within biomass act as catalysts that limit the yield of bio‐oil and alter the product distribution. In this work, the effect of alkaline earth metals on cellulose pyrolysis chemistry was investigated to determine the catalytic effect on primary (transport‐free) and secondary (diffusion‐limited) reaction pathways. The catalytic materials included homogeneous metal ions Ca 2+ and Mg 2+ from their inorganic salts, Ca(NO3 )2 and Mg(NO3 )2, and their corresponding heterogeneous metal oxides, CaO and MgO. Although the oxides had a limited impact on cellulose pyrolysis chemistry, the metal ions altered the secondary reaction pathways of cellulose significantly under diffusion‐limited conditions common to lignocellulosic particles within industrial reactors. Abstract : Naturally catalysis : The catalytic transformation of cellulose with naturally occurring alkaline earth metals such as calcium and magnesium promotes the secondary melt‐phase conversion of volatile products such as levoglucosan to C2 –C4 organic compounds.